2010
DOI: 10.1177/0897190010387933
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge Levels and Opinions of Biomedical Students Regarding the Human Papillomavirus Quadrivalent (Types 6, 11, 16, and 18) Recombinant Vaccine

Abstract: The objective of this research was to assess the knowledge levels and attitudes of all students enrolled in 1 biomedical university regarding the human papillomavirus quadrivalent (types 6, 11, 16, and 18) recombinant vaccine (Gardasil-Merck; the HPV vaccine). A survey of students from all 7 programs at the University was conducted in January 2009. A total of 1120 useable questionnaires were obtained. These programs included pharmacy, osteopathic medicine, physician assistant, physical therapy, occupational th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The questionnaire was based on the literature review. 13,[33][34][35][36][37][38][39][40][41][42] Content and face validity of the instrument were determined via a panel of 7 experts. Panel members included 2 gynecologist, 1 oncologist, 1 infectious diseases expert, and 3 nurse educators.…”
Section: Data Collectionmentioning
confidence: 99%
“…The questionnaire was based on the literature review. 13,[33][34][35][36][37][38][39][40][41][42] Content and face validity of the instrument were determined via a panel of 7 experts. Panel members included 2 gynecologist, 1 oncologist, 1 infectious diseases expert, and 3 nurse educators.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, Walker et al found that only 5.1% (8/158) of dental, dental hygiene, and nursing students knew that HPV vaccines may be effective in protecting against HPV and related oropharyngeal cancer (40). The majority of students in each study knew that the HPV vaccine is safe, though there was a wide range between 75% (751/1002) and 99% (198/200) of HPS with this knowledge (34,39). These results demonstrate that a variety of effective educational strategies for improving knowledge about HPV and HPV vaccination.…”
Section: Knowledgementioning
confidence: 76%
“…The majority of students in each study knew that the HPV vaccine is safe, though there was a wide range between 75% (751/1002) and 99% (198/200) of HPS with this knowledge ( 34 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation